If a circle of radius R passes through the origin O and intersects the coordinate axes at \[A\] and \[B\] , then find the locus of the foot of perpendicular from \[O\] on \[AB\] .
(A) \[{\left( {{x^2} + {y^2}} \right)^2} = 4R{x^2}{y^2}\]
(B) \[\left( {{x^2} + {y^2}} \right)\left( {x + y} \right) = {R^2}xy\]
(C) \[{\left( {{x^2} + {y^2}} \right)^3} = 4{R^2}{x^2}{y^2}\]
(D) \[{\left( {{x^2} + {y^2}} \right)^2} = 4{R^2}{x^2}{y^2}\]
Answer
Verified
387.3k+ views
Hint: We will first find the slope of the foot perpendicular from \[O\] on \[AB\] . As we know that the product of slopes of two perpendicular lines is \[ - 1\] , using this we will find the slope of \[AB\] and then the equation of line \[AB\] . Then we will find the coordinates of \[A\] and \[B\] . At last, we will find the length of \[AB\] and then equate it to the diameter of the circle to find the locus.
Complete step-by-step solution:
Let the foot of perpendicular from \[O\] on \[AB\] be \[P(h,k)\] .
As \[A\] lies on the x-axis, so the y coordinate of \[A\] will be zero. Similarly, \[B\] lies on the y-axis, so the x coordinate of \[B\] will be zero.
Slope of \[OP\]\[ = \dfrac{{k - 0}}{{h - 0}}\]
\[\therefore {\text{Slope of OP}} = \dfrac{k}{h}\]
As \[OP \bot AB\] ,
\[ \Rightarrow {\text{Slope of OP}} \times {\text{Slope of AB}} = - 1\]
On solving, we get
\[ \Rightarrow \dfrac{k}{h} \times {\text{Slope of AB}} = - 1\]
\[\therefore {\text{Slope of AB}} = - \dfrac{h}{k}\]
We know, equation of a line is given by
$y - {y_1} = \dfrac{{{y_2} - {y_1}}}{{{x_2} - {x_1}}}(x - {x_1})$
Hence, equation of \[AB\] is
$y - k = - \dfrac{h}{k}(x - h)$
Putting $x = 0$ ,
$y - k = \dfrac{{{h^2}}}{k}$
On rearranging,
$ \Rightarrow y = \dfrac{{{k^2} + {h^2}}}{k}$
Now, putting $y = 0$ ,
$ - k = - \dfrac{h}{k}\left( {x - h} \right)$
On solving,
$ \Rightarrow \dfrac{{{k^2}}}{h} = \left( {x - h} \right)$
On rearranging,
$ \Rightarrow x = \dfrac{{{k^2} + {h^2}}}{h}$
Now, we can write the coordinates of $A$ and $B$ as
$A\left( {\dfrac{{{k^2} + {h^2}}}{h},0} \right)$ and $B\left( {0,\dfrac{{{k^2} + {h^2}}}{k}} \right)$
Distance between two points $({x_1},{y_1})$ and $({x_2},{y_2})$ is given by $\sqrt {{{({x_1} - {x_2})}^2} + {{({y_1} - {y_2})}^2}} $ .
$\therefore AB = \sqrt {{{\left( {\dfrac{{{k^2} + {h^2}}}{h} - 0} \right)}^2} + {{\left( {0 - \dfrac{{{k^2} + {h^2}}}{k}} \right)}^2}} $
$\because AB = 2R$
$ \Rightarrow \sqrt {{{\left( {\dfrac{{{k^2} + {h^2}}}{h} - 0} \right)}^2} + {{\left( {0 - \dfrac{{{k^2} + {h^2}}}{k}} \right)}^2}} = 2R$
Squaring both sides
\[ \Rightarrow {\left( {\dfrac{{{k^2} + {h^2}}}{h}} \right)^2} + {\left( {\dfrac{{{k^2} + {h^2}}}{k}} \right)^2} = 4{R^2}\]
On solving,
\[ \Rightarrow \dfrac{{{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{h^2}}} + \dfrac{{{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{k^2}}} = 4{R^2}\]
Taking L.C.M.
\[ \Rightarrow \dfrac{{{k^2}{{\left( {{k^2} + {h^2}} \right)}^2} + {h^2}{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{k^2}{h^2}}} = 4{R^2}\]
Taking \[{k^2}{h^2}\] to R.H.S.
\[ \Rightarrow {k^2}{\left( {{k^2} + {h^2}} \right)^2} + {h^2}{\left( {{k^2} + {h^2}} \right)^2} = 4{R^2}{k^2}{h^2}\]
Taking \[{\left( {{k^2} + {h^2}} \right)^2}\] common from L.H.S.
\[ \Rightarrow {\left( {{k^2} + {h^2}} \right)^2}\left( {{k^2} + {h^2}} \right) = 4{R^2}{k^2}{h^2}\]
\[ \Rightarrow {\left( {{k^2} + {h^2}} \right)^3} = 4{R^2}{k^2}{h^2}\]
Now, to find the locus we will replace \[h\] with \[x\] and \[k\] with \[y\] and rearrange,
\[ \Rightarrow {\left( {{x^2} + {y^2}} \right)^3} = 4{x^2}{y^2}{R^2}\]
Therefore, the locus of the foot of perpendicular from \[O\] on \[AB\] is \[{\left( {{x^2} + {y^2}} \right)^3} = 4{x^2}{y^2}{R^2}\] .
Hence, option (C) is correct.
Note: Centre of the circle and the foot of the perpendicular on the line \[AB\] are two distinct points. One might get confused that the foot of the perpendicular is the centre of the circle and also \[A\] lies on the x-axis, so the y coordinate of \[A\] will be zero. Similarly, \[B\] lies on the y-axis, so the x coordinate of \[B\] will be zero.
Complete step-by-step solution:
Let the foot of perpendicular from \[O\] on \[AB\] be \[P(h,k)\] .
As \[A\] lies on the x-axis, so the y coordinate of \[A\] will be zero. Similarly, \[B\] lies on the y-axis, so the x coordinate of \[B\] will be zero.
Slope of \[OP\]\[ = \dfrac{{k - 0}}{{h - 0}}\]
\[\therefore {\text{Slope of OP}} = \dfrac{k}{h}\]
As \[OP \bot AB\] ,
\[ \Rightarrow {\text{Slope of OP}} \times {\text{Slope of AB}} = - 1\]
On solving, we get
\[ \Rightarrow \dfrac{k}{h} \times {\text{Slope of AB}} = - 1\]
\[\therefore {\text{Slope of AB}} = - \dfrac{h}{k}\]
We know, equation of a line is given by
$y - {y_1} = \dfrac{{{y_2} - {y_1}}}{{{x_2} - {x_1}}}(x - {x_1})$
Hence, equation of \[AB\] is
$y - k = - \dfrac{h}{k}(x - h)$
Putting $x = 0$ ,
$y - k = \dfrac{{{h^2}}}{k}$
On rearranging,
$ \Rightarrow y = \dfrac{{{k^2} + {h^2}}}{k}$
Now, putting $y = 0$ ,
$ - k = - \dfrac{h}{k}\left( {x - h} \right)$
On solving,
$ \Rightarrow \dfrac{{{k^2}}}{h} = \left( {x - h} \right)$
On rearranging,
$ \Rightarrow x = \dfrac{{{k^2} + {h^2}}}{h}$
Now, we can write the coordinates of $A$ and $B$ as
$A\left( {\dfrac{{{k^2} + {h^2}}}{h},0} \right)$ and $B\left( {0,\dfrac{{{k^2} + {h^2}}}{k}} \right)$
Distance between two points $({x_1},{y_1})$ and $({x_2},{y_2})$ is given by $\sqrt {{{({x_1} - {x_2})}^2} + {{({y_1} - {y_2})}^2}} $ .
$\therefore AB = \sqrt {{{\left( {\dfrac{{{k^2} + {h^2}}}{h} - 0} \right)}^2} + {{\left( {0 - \dfrac{{{k^2} + {h^2}}}{k}} \right)}^2}} $
$\because AB = 2R$
$ \Rightarrow \sqrt {{{\left( {\dfrac{{{k^2} + {h^2}}}{h} - 0} \right)}^2} + {{\left( {0 - \dfrac{{{k^2} + {h^2}}}{k}} \right)}^2}} = 2R$
Squaring both sides
\[ \Rightarrow {\left( {\dfrac{{{k^2} + {h^2}}}{h}} \right)^2} + {\left( {\dfrac{{{k^2} + {h^2}}}{k}} \right)^2} = 4{R^2}\]
On solving,
\[ \Rightarrow \dfrac{{{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{h^2}}} + \dfrac{{{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{k^2}}} = 4{R^2}\]
Taking L.C.M.
\[ \Rightarrow \dfrac{{{k^2}{{\left( {{k^2} + {h^2}} \right)}^2} + {h^2}{{\left( {{k^2} + {h^2}} \right)}^2}}}{{{k^2}{h^2}}} = 4{R^2}\]
Taking \[{k^2}{h^2}\] to R.H.S.
\[ \Rightarrow {k^2}{\left( {{k^2} + {h^2}} \right)^2} + {h^2}{\left( {{k^2} + {h^2}} \right)^2} = 4{R^2}{k^2}{h^2}\]
Taking \[{\left( {{k^2} + {h^2}} \right)^2}\] common from L.H.S.
\[ \Rightarrow {\left( {{k^2} + {h^2}} \right)^2}\left( {{k^2} + {h^2}} \right) = 4{R^2}{k^2}{h^2}\]
\[ \Rightarrow {\left( {{k^2} + {h^2}} \right)^3} = 4{R^2}{k^2}{h^2}\]
Now, to find the locus we will replace \[h\] with \[x\] and \[k\] with \[y\] and rearrange,
\[ \Rightarrow {\left( {{x^2} + {y^2}} \right)^3} = 4{x^2}{y^2}{R^2}\]
Therefore, the locus of the foot of perpendicular from \[O\] on \[AB\] is \[{\left( {{x^2} + {y^2}} \right)^3} = 4{x^2}{y^2}{R^2}\] .
Hence, option (C) is correct.
Note: Centre of the circle and the foot of the perpendicular on the line \[AB\] are two distinct points. One might get confused that the foot of the perpendicular is the centre of the circle and also \[A\] lies on the x-axis, so the y coordinate of \[A\] will be zero. Similarly, \[B\] lies on the y-axis, so the x coordinate of \[B\] will be zero.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE